2010
DOI: 10.5014/ajot.2010.09153
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation for Bilateral Amputation of Fingers

Abstract: We describe reconstructive surgeries, therapy, prostheses, and adaptations for a patient who experienced bilateral amputation of all five fingers of both hands through the proximal phalanges in January 1992. The patient made considerable progress in the use of his hands in the 10 mo after amputation, including nearly a 120% increase in the active range of flexion of metacarpophalangeal joints. In late 1992 and early 1993, the patient had "on-top plasty" surgeries, in which the index finger remnants were transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The remaining neurorehabilitationrelated articles spanned a diversity of topics. Three assessed the effectiveness of creative adaptive devices for improving function (Carver, 2009;Glasgow et al, 2012;Stapanian et al, 2010), and another examined the use of gel pads to prevent pressure sores (Thorne et al, 2009). Hall et al (2013) evaluated whether a conservative approach to treatment of carpal tunnel syndrome would reduce surgical intervention and found that patients in the conservative intervention group reported greater symptom relief.…”
Section: Descriptive; Anovasmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining neurorehabilitationrelated articles spanned a diversity of topics. Three assessed the effectiveness of creative adaptive devices for improving function (Carver, 2009;Glasgow et al, 2012;Stapanian et al, 2010), and another examined the use of gel pads to prevent pressure sores (Thorne et al, 2009). Hall et al (2013) evaluated whether a conservative approach to treatment of carpal tunnel syndrome would reduce surgical intervention and found that patients in the conservative intervention group reported greater symptom relief.…”
Section: Descriptive; Anovasmentioning
confidence: 99%
“…An additional scoping review (2%) was performed by Hand et al (2011). A total of 15 articles (36%) described single-subject or case designs that used 2 or fewer participants (Beckelhimer et al, 2011;Carver, 2009;Ciro et al, 2013;Earley et al, 2010;Hardy et al, 2010;Henshaw et al, 2011;Hermann et al, 2010;Jack & Estes, 2010;Preissner, 2010;Rowe et al, 2009;Skubik-Peplaski et al, 2012;Sledziewski et al, 2012;Stapanian et al, 2010;Wu et al, 2011;Zlotnik et al, 2009). See Table 3 for additional information regarding participant numbers for the studies reviewed.…”
Section: Designs Usedmentioning
confidence: 99%
“…Only 1 stroke effectiveness study specifically addressed a different area of impairment poststroke-cognitive dysfunction (Rand, Weiss, & Katz, 2009). The remaining effectiveness studies (n 5 5) involved hand injury (Hall, Lee, Page, Rosenwax, & Lee, 2010;Stapanian, Stapanian, & Staley, 2010), arthritis ( Jack & Estes, 2010), lymphedema (McClure, McClure, Day, & Brufsky, 2010, and acute care rehabilitation (Thorne, Sauve, Yacoub, & Guitard, 2009). Although collectively, the studies related to rehabilitation, disability, and participation published in AJOT during this period demonstrate that occupational therapy researchers are producing evidence, some concerns need to be addressed related to becoming evidence based in this practice area.…”
Section: Rehabilitation Disability and Participation Research Publimentioning
confidence: 99%
“…Of the 20 effectiveness studies published by AJOT in 2009 and 2010 related to rehabilitation, disability, and participation, nearly half (n 5 9) were case studies (Carver, 2009;Earley et al, 2010;Hardy et al, 2010;Hermann et al, 2010;Jack & Estes, 2010;Preissner, 2010;Rowe et al, 2009;Stapanian et al, 2010;Zlotnik et al, 2009). Moreover, 4 studies had <10 participants per intervention group evaluated (Giuffrida et al, 2009;Hall et al, 2010;Hayner et al, 2010;Rand et al, 2009).…”
Section: Preponderance Of Case Studies and Studies With Small Sample mentioning
confidence: 99%
See 1 more Smart Citation